Analisis Faktor-Faktor yang Mempengaruhi Kinerja Keuangan Lembaga Perkreditan Desa di Kabupaten Badung - Nareswari, Anak Agung Sagung Indah; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 31 No 10 (2021)DO - 10.24843/EJA.2021.v31.i10.p17, 2021)
Financial institutions have an important role in improving the country's economy, one of which is the LPD. This study aims to analyze the factors that affect the financial performance of LPDs in Badung Regency. The number of samples taken was 87 LPDs in Badung Regency with a probability sampling method. The data collection method used was a survey method by distributing questionnaires. The analysis technique used is multiple linear regression. The results of this study indicate that the principles of good governance, namely transparency, accountability, responsibility, independence, fairness and competence of human resources consisting of knowledge, skills, and attitudes have a positive effect on financial performance. The results of this study are expected to be able to provide additional information for parties who have a direct role in improving financial performance to carry out their duties properly so that they will be able to produce quality financial performance. Keywords: Financial Performance; Good Governance Principles; Human Resources Competence.